numbers of PFCanti-HBc in patients with chronic Hepatitis - Baghdad Science Journal (مجلة بغداد للعلوم)
plaque forming assay was used enumerate the number of plaque forming cells of anti-HBc in eight patintes with chronic hepatitis and eight health